Challenge of understanding and dealing with bacterial vaginosis - Giraldo, Paulo Cesar; Passos, Mauro Romero L; Bravo, Renato; Varella, Renata Q; Campos, Wilma NA; Amaral, Rose Luce do; Marussi, Emílio (Brazilian Journal of Sexually Transmitted Diseases, 2007)
The aim of this article is to conduct an extensive revision on the subject bacterial vaginosis and the challenge of taking care of the women with suchan illness. The authors describe the subject from the historical, epidemical and phyisiopathogenical aspects even the clinical and laboratorial evalua-tions, clinical and microbiological cure criteria and the interrelation with pregnancy. The reader is given a global vision of the subject from a didaticand pratical perspective. Various current aspects that analyse the little known physiopathogenesis of the disease nowadays are also presented. Topicssuch as mannose-binding lecetin (MBL) and toll like receptor 4 (TLR-4) are discussed based on the latest and most updated knowledge in interna-tional literature.